Effect of temperature by infrared thermal treatment on the rice bran qualities - N Jaianong; P Choomjaihan (My University, 2019)
Abstract The objective of this research was to study the effect of the infrared heat treatment on the qualities of the rice bran. The rice bran with the initial moisture content of 12.9 %g water ·g −1 dry matter was heated under the high temperature generated from infrared radiation at 60, 80, 100, 120 and 140°C respectively and the target moisture content of rice bran after being heated was 5 % g water ·g −1 dry matter . The optimum condition of thermal treatment of rice bran respect to the quality of extracted oil and the energy consumption was determined. The results showed that the rice bran oil was extracted more at 140°C heat treatment than other temperature; additionally, the free fatty acid in extracted rice bran oil was smallest in amount. Nevertheless, the concentration of gamma oryzanol was not difference throughout the experiment. The mathematical model of drying kinetics was examined, and the appropriate model was the Logarithmic model which the R 2 of 0.9955 – 0.9994 and the RMSE of 1.5×10 −5 -6.3×10 −5
Keywords: Rice bran oil; Spectroscopy and Chemometric Analyses